Effect of short-term fattening period and castration method on productivity, serum testosterone, and economic efficacy in Hanwoo cattle - Ahn, Jun Sang; Kwon, Eung Gi; Lee, Hyun Jeong; Kim, Ui Hyung; Won, Jeong Il; Jang, Sun Sik; Park, Byung Ki (Journal of animal science and technology, 2023)
The purpose of this study was to evaluate the effects of castration method and short-term fattening periods on Hanwoo cattle. Thirty-two Hanwoo calves (average body weight: 148.4 ± 19.8 kg) were used. The calves were randomly assigned in a 2 × 2 factor according to two castration methods (castration or hemi-castration) and two short-term finishing periods (24 months or 26 months). The final body weight increased significantly as the fattening period increased ( < 0.05), and the average daily weight gain was higher in the hemi-castration groups than in the castration groups ( < 0.05). After surgical castration, testosterone concentration was higher in the hemi-castration group than in the castration group during the entire experimental period ( < 0.05). The rib eye area was wider in the hemi-castration group than in the castration group ( < 0.01).An interaction effect was observed between the castration method and short-term fattening period ( < 0.05). Marbling and auction price scores differed between castration methods and were higher in the castration group than in the hemi-castration group ( < 0.01). Gross receipts and net income increased in the castration group compared to the hemi-castration group ( < 0.01) and showed a tendency to increase with the short-term fattening period, but there was no significant difference. Thus, castration to remove both testicles is essential for economic profit through producing high-quality Korean beef meat, and short-term fattening for 26 months, rather than 24 months, can benefit more by increasing carcass weight and meat quality.